A Critical Reading of the Major Introductions to understanding the West and its Determinants: A systematic attempt to establish the Occidentalism - BOUCHAIR, AbdulAziz Fodil (Journal of Humanities & Social Sciences, 2023)
The subject of the research is one of the civilizational studies that investigates the subject of the West and seeks to establish the science of Occidentalism. This is with the aim of asking about the major introductions to study it and analyze its general determinants that we should adopt in study and understanding, in order to reveal the relationship between the West as a cognitive and behavioral system and its colonial tendency that it practiced on the world. Through it, we discuss the arrogant psychological characteristics that distinguished the Western man, and how he ruled the world with his thought, and his vision of the world that determined his attitudes towards the other and was reflected in his relationships and behaviors in reality. In addition to clarifying the impact of all this on the world in terms of disrupting its civilized renaissance and exploiting its material and human wealth, and directing the movement Individuals and peoples in the direction that the West wants, in a way that guarantees its interests and meets its needs. We relied on the analytical and critical approaches in our study of this topic. We came up with the following conclusions and recommendations: the need to identify the major introductions to studying the West and analyzing it critically, and to clarify its general determinants, such as the colonial and psychological determinants, and their consequences in the history of the modern and contemporary world. In addition to the need to build curricula for getting to know the West and how to overcome, it in order to avoid the causes of its weakness and the factors of its decline, and the conscious endeavor to open alternative paths to it based on new models in thought, method, and life.